A deep dive into worker psychological well-being in the construction industry: A systematic review and conceptual framework - Li, Keyao (Eden); Wang, Dan; Sheng, Zitong; Griffin, Mark (2022)
The construction industry is stressful and concerns for workers' psychological well-being (PWB) are on the rise with the high prevalence of mental health problems. However, there is currently no clear framework or system in the mainstream construction literature to guide management practices such as allocating resources, optimizing work systems, and supporting worker well-being. In this study, a state-of-the-art review was conducted on PWB constructs and the associated theoretical perspectives. This review of theories and dimensions aims to provide a more complete account of the factors associated with PWB and provide more systemic guidance for organizations. Drawing on a three-dimensional taxonomy of PWB in social science literature, this study identified five themes of PWB antecedents in the construction community: motivational, relational, working environment, personal attributes, and social cognitive. Findings in this study could contribute to both PWB theory development and management practices. Theoretically, this review introduced more clarity to PWB theories in the construction literature, linking different dimensions of PWB constructs with their antecedents. This also allows for identifying future research avenues to expand the boundaries of the existing body of knowledge. Practically, management practices are offered to support management, policy makers, and decision makers to optimize and improve health and well-being strategies in the construction industry.